La Familia Frente A Las Conductas Adictivas De Los Niños Y Adolescentes De La Comunidad Terapéutica Los Chilalos - Carrión Medina, Suliana Gicela (2016)
This research is part of a study on the Therapeutic Community The Chilalos about "THE DYSFUNCTIONAL FAMILIES AND ITS IMPACT ON ADDICTIVE BEHAVIOR OF CHILDREN AND ADOLESCENTS" whose purpose is part of strengthening family relationships through a Plan Social Intervention that enables the reduction of addictive behaviors. Among the key findings was determined that there dysfunctional families fully involved in the sector. Inadequate, violence within the family and the influences of friends are the main causes of addiction in children and adolescents and its consequences are part of the deterioration of his health, behavior or negative behavior Conduct, besides causing a rift family, breakdown of relationships, which certainly cause social isolation, and thus low self-esteem. It should be noted that according to the results obtained, it appears that the family is the primary agent in the recovery process of their children and the support they receive from them will ensure overcoming addictions. During the investigation techniques that enabled a diagnosis on the subject of study, such as direct observation, interview, and survey to gather information and test criteria stakeholders, was used where it is revealed that family dysfunction is the most important issue, compared to addictive behaviors presented by children and adolescents. Product research the theoretical foundations related to the topic of study establishing causes and consequences of the problem, also allowed the development of a proposal for intervention were built social "A New Beginning". This research process is supported in the Methodology of Community Self-Development, including children, teenagers and parents to promote attitudes for adequate performance in family life and likewise strengthen spiritual moral and ethical values that improve family relationships.